Synthesis of Sum-and-Difference Patterns for Radome-Enclosed Linear Arrays With Common Weights Using Convex Optimization - Li, Wei-Zong; Jiao, Yong-Chang; Zhang, Yi-Xuan; Zhang, Li (IEEE antennas and wireless propagation letters, 2025)
With the advancement of monopulse radar technology, synthesis of the sum-and-difference patterns (SDPs) for the radome-enclosed arrays has emerged as a pressing area of research. Due to the influence of asymmetric radome, active element patterns of the radome-enclosed linear array (RELA) are completely different. To accurately consider the array-element mutual couplings and array-and-radome interactions, a novel simultaneous synthesis technique for low-sidelobe-level (SLL) SDPs of the RELA with common weights is proposed. First, a nonconvex SDP synthesis problem with the nonconvex constraint and the nonconvex objective function is established. Then, by fixing the reference phases for the sum pattern (SP) radiation far-field and the difference pattern (DP) slope at the target direction, the original nonconvex synthesis problem is transformed into a convex minimum problem, which can be efficiently solved by the convex optimization methods. Finally, a 40-element RELA is implemented, demonstrating that the proposed synthesis technique can be used to simultaneously synthesize SDPs of the RELA with asymmetric active element patterns. The SPs with −25 dB SLL and the DPs with −20 dB SLL are simultaneously synthesized, and the obtained results verify effectiveness of the proposed synthesis technique.